The Diffusion of Shopping Innovation in Metaverse: Opportunities and Challenges in Indonesia - Emaridial Ulza; Mohammad Hamsal; Asnan Furinto; Rano Kartono (Agregat: Jurnal Ekonomi dan Bisnis, 2022)
In the future, the development of the artificial world (Metaverse) is expected to affect how consumers spend and will affect geopolitical, socioeconomic, and education. The Research wants to describe how these three things become challenges and opportunities for companies and governments in developing business in the second life metaverse by looking at the diffusion of innovation theory